Disulfonimide catalyzed asymmetric intramolecular hydroamination of alkenyl thioureas: Concentration effect in the hydroamination. (13th August 2021) - Takagi, Ryukichi; Duong, Duyen Thi; Ichiki, Toshiya
Abstract: Disulfonimide (DSI)-catalyzed asymmetric intramolecular hydroamination of alkenyl thiourea was examined. The reaction proceeded even under dilute concentrations and high temperatures, and the hydroamination product was obtained with good chemical yield and moderate enantioselectivity. The density functional theory (DFT) calculations on the reaction supported the mechanism in which the thiourea moiety of the alkenyl amine acted as a dual hydrogen bond donor. Graphical abstract: Image 1 Highlights: Disulfonimide-catalyzed asymmetric intramolecular hydroamination of alkenyl thiourea was examined. The hydroamination product was obtained with good chemical yield and moderate enantioselectivity. The reaction proceeded under dilute without stirring. The mechanism, in which the thiourea moiety acted as a hydrogen bond donor, was proposed.